Microwave-Assisted Synthesis of Hydroxybenzylidene-Andrographolides and Its Inhibitory Activity against HIV-1 Protease - Sandra Megantara & , Halimah Halimah, Annisa Putrianty, Daryono Hadi Tjahjono, Rahmana Emran Kartasasmita, Maria Immaculata Iwo, Jutti Levita, Slamet Ibrahim (Journal of Applied Pharmaceutical Science, 2018)
Andrographolide, a lacton diterpenoid, due to its many biological activities, was subjected to a semi-synthetic work by reacting andrographolide (a) with hydroxybenzaldehyde under microwave irradiation. This reaction led to three new andrographolide analogues, which are 3,19-2-hydroxybenzylidene andrographolide (b), 3,19-3-hydroxybenzylidene andrographolide (c), and 3,19-4-hydroxybenzylidene andrographolide (d), respectively. The yields were 85%, 86%, 86% for compounds b, c, d respectively. These new compounds had already been studied previously by pharmacophore screening and molecular docking simulation, which revealed their affinity to HIV-1 protease. Furthermore, their inhibitory activity against HIV-1 protease was measured by in vitro fluorometric method at (Ex/Em) = 330/450 nm which resulted 18.14, 10.72, 9.93, 8.32 μM respectively for IC50 value. The increased activity of these compounds may reflect the binding of the hydroxybenzaldehyde moiety with the hydrophobic area of the HIV-1 protease.
Keywords: Andrographolide, ARVs,HIV, HIV-1 protease inhibitors,hydroxybenzylideneandrographolide.